How to Make Diagnosis Related Groups Payment More Feasible in Developing Countries- A Case Study in Shanghai, China. - Zhaoxin Wang; Rui Liu; Ping Li; Chenghua Jiang; Mo Hao (Tehran University of Medical Sciences, 2014)
Given limited health sources, how to make DRGs (Diagnosis Related Groups) more feasible is a big question in developing countries. This study contributes to the debate on how to bridge the pay-for-service and DRGs during the transitional period of payment reform.From 2008 to 2012, 20740 patients with cirrhosis or duodenal ulcer disease were chosen as sample. Using multiple linear regression analysis, the interrelationships between the total medical expenses of the inpatients, and age, gender of the inpatients, length of stay (LOS), region and economic level of the hospitals were examined.The main findings were 1) length of stay (LOS) and the economic level of treatment location had a statistically significant impact on patients with cirrhosis or duodenal ulcer disease. Meanwhile gender is not a significant factor for both of them. 2) Under the premise of limited resources, developing countries should first narrow down to screen for common and frequently occurring diseases, then study the key factors which affect the treatment cost of the diseases.Based on picking out common diseases and their key factors, Simplification of the DRGs setting process will greatly increase the efficiency of implementing DRGs in the developing world.